2013
DOI: 10.3109/09553002.2013.784423
|View full text |Cite
|
Sign up to set email alerts
|

Late effects on the health-related quality of life in a cohort population decades after environmental radiation exposure

Abstract: Being female and less than 12 years of age at disclosure were more significant predictors of HRQoL scores than the levels of radiation exposure among people exposed to protracted low-dose radiation. Further studies are needed to determine the psychological distresses, such as depression and anxiety, and their relationships in this case, especially for the most vulnerable young females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…A previous study indicated that the exposed population exhibited significantly lower health-related quality of life (HRQoL) scores in the physical, psychological, and social relationship domains than did unexposed members of the general population in the same city (Yen et al 2011). Furthermore, the HRQoL scores were similar amongst those who were exposed to various amounts of cumulative radiation, and women and those who were informed of the exposure at or before the age of 12 years demonstrated relatively lower HRQoL scores (Yen et al 2013). The aetiology of the poor HRQoL scores amongst members of the Taiwan RCB cohort remains unclear, but might be related to increased chronic psychological stress or posttraumatic stress symptoms; such symptoms have been identified amongst other cohorts exposed to radiation such as those living near the Three Mile Island power plant (Dew and Bromet 1993) or those involved in the accident at the Chernobyl nuclear power plant (Bromet and Havenaar 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study indicated that the exposed population exhibited significantly lower health-related quality of life (HRQoL) scores in the physical, psychological, and social relationship domains than did unexposed members of the general population in the same city (Yen et al 2011). Furthermore, the HRQoL scores were similar amongst those who were exposed to various amounts of cumulative radiation, and women and those who were informed of the exposure at or before the age of 12 years demonstrated relatively lower HRQoL scores (Yen et al 2013). The aetiology of the poor HRQoL scores amongst members of the Taiwan RCB cohort remains unclear, but might be related to increased chronic psychological stress or posttraumatic stress symptoms; such symptoms have been identified amongst other cohorts exposed to radiation such as those living near the Three Mile Island power plant (Dew and Bromet 1993) or those involved in the accident at the Chernobyl nuclear power plant (Bromet and Havenaar 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Among many health and well-being studies relevant to the present work, the WHOQOL-BREF has been widely used to assess vulnerable communities living in impoverished "high-risk" environments. These include slums (Skevington, 2009;Simonelli et al, 2013), refugee camps (Akinyemi et al, 2012), earthquake zones (Ardalan et al, 2011;Guo et al, 2012;Valenti et al, 2013), radiation sites (Yen et al, 2013), political conflict areas (Hammoudeh et al, 2013), and torture victims (Pabilonia et al, 2010). This body of research illustrates how adversity affects QoL in very diverse cultures, and this type of evidence could assist in delivering an appropriate humanitarian response.…”
Section: Introductionmentioning
confidence: 99%
“…As yet, the WHOQOL-BREF’s responsiveness has not been comprehensively examined with regard to a variety of situations and populations, despite several studies which assessed outcomes after diverse interventions and major life events. Examples include radiation exposure, 28 earthquake survival, 29 housing elderly Sichuan Chinese in an earthquake zone, 30 Palestinian conflict in Gaza, 31 Nigerian refugees, 32 women torture survivors, 33 slum upgrades 34 and poverty in low/middle-income countries. 35 By using the WHOQOL-BREF in these challenging fields, this indicates that social and development practitioners view it as a suitable tool.…”
Section: Introductionmentioning
confidence: 99%